The face of Jizo: image and cult in medieval Japanese buddhism - Glassman, Hank (Univ. of Hawai'i Press, 2012)
The iconology of Jizō -- Kasuga, Jizō, and Kamakura Ritsu -- The Jizō dance : ecstasy, possession, and performance -- Stones, fertility, and the unconnected